An Objective Evaluation of the Upper Eyelid Position after Phacoemulsification Cataract Surgery - Marqués-Fernández, Victoria; Garcia-Zamora, Maria; Calabuig-Goena, Maria; Diez-Montero, Cecilia; Schellini, Silvana A. [UNESP]; Khandekar, Rajiv; Galindo-Ferreiro, Alicia (Taylor & Francis, 2019)
Purpose: To objectively measure the upper eyelid position following phacoemulsification cataract surgery and to identify the determinants of postoperative transient ptosis. Methods: This is a single arm prospective study of patients who underwent cataract surgery from January to May 2017 at a tertiary Eye Hospital in Spain. Data comprised of: the type of anesthesia, the duration that the speculum remained in place and the total surgical time (duration of the procedure). The total surgical time was defined as, the time from the beginning of the paracentesis to the closure of the wounds (incision time). Digital photographs were obtained of: the face with the eye in primary gaze, looking inferiorly and superiorly, preoperatively, and 1, 30, 90 and 180 days postoperatively. Measurements for eyelid crease, levator function, and marginal reflex distance 1 (MRD1) were performed using ImageJ. Statistical analysis was performed of the difference between the preoperative and postoperative measurements. Results: The study consisted of 112 patients. The median lid crease was 9.0 mm [IQR (interquartile range) 7.5; 10.0] both preoperatively and at 180 days postoperatively (IQR 8.0; 10.8). No statistical difference was determined in the lid crease measurements between these two times (P =.17). The median levator function differed significantly preoperatively, at day 1 and 30, 60 and 180 days postoperatively (P <.01). MRD1 decreased significantly from a median of 3.01 mm preoperatively to 2.7 mm at 30 days postoperatively (P =.05) but was similar at preoperative and after 180 days (P =.7). The correlation of MRD1 to the duration of the speculum in place (P =.2) and the incision time (P =.57) was not significant. Conclusions: Ptosis, following phacoemulsification cataract surgery, is mild and transient, occurring only in the early postoperative period.
Keywords: blepharoptosis; cataract; eyelid; Phacoemulsification; surgery